Relationships between sleep patterns and metabolic profile in patients maintained on antipsychotics: a cross-sectional comparative study - Kiwan N; Mahfoud Z; Ghuloum S; Yehya A; Hammoudeh S; Hani Y; Chamali R; Amro I; Mook-Kanamori D; Al-Amin H (Neuropsychiatric Disease and Treatment, 2019)
Nancy Kiwan,1 Ziyad Mahfoud,2,3 Suhaila Ghuloum,4 Arij Yehya,1 Samer Hammoudeh,1 Yahya Hani,4 Rifka Chamali,1 Iman Amro,1 Dennis Mook-Kanamori,5 Hassen Al-Amin61Department of Research, Weill Cornell Medicine - Qatar, Doha, Qatar; 2Department of Health Policy and Research, Weill Cornell Medicine - Qatar, Doha, Qatar; 3Department of Healthcare Policy and Research, Weill Cornell Medicine, New York, NY, USA; 4Psychiatry Hospital, Hamad Medical Corporation, Doha, Qatar; 5Department of Physiology and Biophysics, Weill Cornell Medicine - Qatar, Doha, Qatar; 6Department of Psychiatry, Weill Cornell Medicine - Qatar, Doha, QatarBackground: Disturbances in sleep duration and quality have been associated with obesity and other metabolic changes. Patients with mental disorders (MD) are known to have more sleep problems, and antipsychotics (AP), used in the treatment of these patients, can also cause weight gain. This study aimed to compare the self-reported sleep patterns between psychiatric patients (on or off AP) and controls. We also evaluated the associations between the clinical and metabolic profiles with short or long sleep duration.Methods: A total of 339 subjects was recruited: Mentally ill patients maintained on AP for at least six months (MD+AP, n=112), patients not taking AP for at least the last six months before enrollment (MD/noAP, n=101), and non-psychiatry controls (HC, n=126). Multinomial regression analysis was applied to find the predictors of irregular sleep duration in this sample.Results: More mentally ill patients (MD+AP and MD/noAP) reported a sleep duration of >8 hrs than HC. Patients from MD/noAP showed more insomnia than HC. Sleep disturbances were significantly more frequent in MD+AP than HC. Participants who reported sleeping >8 hrs had higher body mass index and waist circumference than those who slept <7 hrs.Conclusion: Female gender, central obesity and being mentally ill were independently associated with long sleep duration (>8h) in the population of Qatar.Keywords: sleep duration, sleep quality, metabolic syndrome, mental disorders, antipsychotics